A new dipeptide as a selective gelator of Cu(ii), Zn(ii), and Pb(ii). Issue 45 (6th November 2020) - Kumar, Santosh; Nandi, Sujay Kumar; Suman, Saurav; Haldar, Debasish
Abstract : Metallogelation was observed selectively for CuSO4, ZnSO4 and Pb(OAc)2 and a dipeptide containing N -phenylglycine and l -Phe, whereas other metals and analogue dipeptides failed to form gel. Abstract : The various aspects associated with the incorporation of steric constraints into a series of dipeptides have been studied. The self-assembly propensities of the dipeptides carried out with the use of complementary experimental methods enabled us to determine the effect of steric constraints. Gly and Aib containing peptide 1 shows a flake-like morphology. The replacement of Gly by l -Phe in peptide 2 increases the steric constraints and results in development of microrods. Peptide 3 with N -phenylglycine and l -Phe has a flower-like morphology, and peptide 4 with N -phenylglycine and l -Tyr has a microsphere morphology. The solid-state FT-IR studies show that the peptides self-assemble by hydrogen bonding. From X-ray crystallography, peptide 1 adopts a kink-like conformation and forms a supramolecular anti-parallel sheet-like structure through multiple intermolecular hydrogen bonds. The replacement of Gly by l -Phe helps peptide 2 to adopt an S-shape conformation and self-assemble to form a supramolecular helix in the solid state. Single crystal X-ray diffraction results exhibit that peptide 3 adopts an extended conformation and forms a 2D sheet-like matrix through π–π stacking interactions. Moreover, metallogelation of peptide 3 was observed selectively for CuSO4 ·5H2 O, ZnSO4 ·7H2 O and Pb(OAc)2 ·3H2 O, whereas other metals were not able to form gel. This study revealed a pivotal role played by the phenyl group in the diverse self-assembly of dipeptides.